The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.3390/ijerph15102205
|View full text |Cite
|
Sign up to set email alerts
|

Translation and Test–Retest of the Spanish Podiatry Health Questionnaire (PHQ-S)

Abstract: Background: The Podiatric Health Questionnaire (PHQ) is a health-related questionnaire consisting of six questions designed for measuring foot health status. To date, the PHQ has only been validated in the English-language version. Thus, this study aimed to perform the Spanish translation and test–retest procedures of the PHQ (PHQ-S). Method: The forward/backward translation and test–retest reliability methods were applied from English to Spanish languages. Regarding the total score for each domain, internal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…That situation emphasises a call for foot checking it must develop by different clinical professionals, beside the foot medical management, to avoid disorders presence and feet estate. Accordingly similar research in subjects with foot disorders [24,25], foot pain [26], and neurological disorders such as Alzheimer disease [27], our results also founded that shoes and physical activities, could take part an essential aspect in the QoL respect in well-being foot in haemophilic subjects. That situation can be the main important question that would allow the development of the well-being QoL and in haemophilic population.…”
Section: Discussionsupporting
confidence: 82%
“…That situation emphasises a call for foot checking it must develop by different clinical professionals, beside the foot medical management, to avoid disorders presence and feet estate. Accordingly similar research in subjects with foot disorders [24,25], foot pain [26], and neurological disorders such as Alzheimer disease [27], our results also founded that shoes and physical activities, could take part an essential aspect in the QoL respect in well-being foot in haemophilic subjects. That situation can be the main important question that would allow the development of the well-being QoL and in haemophilic population.…”
Section: Discussionsupporting
confidence: 82%
“…Our results did not show statistically significant differences related to foot pain [ 5 , 8 ]. These findings are different, with similar research reported on subjects with foot pain [ 1 ], as well as with foot pain [ 27 ] as measured by employing the visual analogic scale (VAS) to determine the sex differences in healthy subjects with foot problems.…”
Section: Discussionmentioning
confidence: 65%
“…The subject was asked to place a vertical slash across the line where appropriate. The reliability and validity of this scale have been tested extensively and found to be moderately valid compared to other pain measures in many studies [29,30].…”
Section: Subjective Painmentioning
confidence: 99%